Criminological Analysis Of Electronic Ticketing (ETLE) - Rafsanai, Ade Rifkah; Hasbi, Hasnan; Faisal, Muhammad (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to identify and analyze the factors contributing to violations of Electronic Traffic Ticketing (ETLE) by road users within the jurisdiction of Polrestabes Makassar from a criminological perspective. An empirical juridical research approach is applied in this study. The research data is obtained from various sources, including but not limited to: in-depth interviews, surveys, observations, books, documents, relevant laws and regulations, and other written materials. The findings of this study indicate that the factors causing ETLE violations in the jurisdiction of Polrestabes Makassar are complex and involve multiple elements, such as individual awareness, social influence, infrastructure limitations, and technological weaknesses. A holistic approach is necessary to understand and address these issues, including public education, infrastructure improvements for ETLE, and advances in violation detection technology. The study recommends a holistic approach to addressing the causes of ETLE violations in the jurisdiction of Polrestabes Makassar. This includes enhancing public education, increasing the number of cameras in strategic locations, and developing more advanced detection technologies. Regular evaluations of ETLE implementation are essential to identify weaknesses and potential improvements, supported by routine training for officers and strengthening inter-agency collaboration. Furthermore, by recognizing and rewarding drivers who comply with traffic regulations, we can create safer and more orderly roads for everyone.